Conflict-Driven User-Generated Content in the Viral Majapahit Laundry Conflict on TikTok - Ayu Rohmayanti, Siti Alfia; Utami, Tri (AKSIOMA : Jurnal Manajemen, 2026)
This study aims to analyze the formation of Conflict-Driven User-Generated Content (CD-UGC) in viral Laundry Majapahit content on TikTok and explain how digital conflict shapes user engagement, sense-making processes, and consumer responses toward a brand. A qualitative approach using netnography was employed to examine user comments posted on four viral TikTok videos of Laundry Majapahit. Data were collected through non-participant observation of comments that had undergone a data-cleaning process and were analyzed using thematic analysis supported by NVivo 12 Plus through stages of open coding, axial coding, and selective coding. The findings identified five major themes underlying the formation of CD-UGC: Emotional Engagement, Marketing Attribution, Sense-Making Process, Community Interaction, and Consumer Response. Emotional Engagement emerged as the most dominant theme, characterized by humor, sarcasm, empathy, and users’ tendency to engage with online conflict. Furthermore, the conflict generated perceptions of gimmicks, sponsorship, and staged content; stimulated curiosity about the dispute; fostered interactions among users; shaped brand perceptions; and increased users’ intentions to try the service and imitate Laundry Majapahit’s communication strategy. These findings demonstrate that digital conflict generates not only online conversations but also Conflict-Driven User-Generated Content, which expands organic reach, strengthens audience engagement, and have the potential to enhance brand virality while creating organic marketing value for businesses. This study contributes to the digital marketing literature by introducing Conflict-Driven User-Generated Content as a conceptual mechanism explaining how online conflict evolves into organic virality within social media ecosystems.